Factors that affect inpatients' quality of sleep - Costa, Shíntia Viana da; Ceolim, Maria Filomena (Revista da Escola de Enfermagem da USP, 2013)
The aim of this study was to identify factors that interfere with the sleep quality of patients admitted to a university hospital in a city in the state of São Paulo, Brazil. This was an exploratory, crosssectional study using non-probability sampling. Participants were 117 patients (59% men, mean age 48.0 years, standard deviation 16.9) hospitalized for at least 72 hours in stable clinical condition. The data were collected with an identification questionnaire and the Factors Affecting Sleep Quality (FASQ) questionnaire. Data processing was performed with descriptive statistics; each item of the FASQ underwent a test and a retest. The factors most often reported were waking up early (55.6%), disrupted sleep (52.1%), excessive lighting (34.2%), receipt of care by nursing staff (33.3%) and organic disorders such as pain and fatigue (26.5%). It is suggested that nurses should plan interventions to modify factors that require intense noise and lighting at night in order to reduce disruption and, consequently, sleep deprivation among patients.